1998
DOI: 10.1143/jjap.37.4439
|View full text |Cite
|
Sign up to set email alerts
|

Electrooptical and Response/Relaxation Properties of Liquid Crystal Cells in In-plane Switching Mode with Polyvinylcinnamate Photoinduced Alignment Layer

Abstract: Using polyvinylcinnamate (PVCi) photoinduced alignment layers and rubbed polyvinylalcohol (PVA) alignment layers, we produced PVCi-PVA and PVA-PVA in-plane switching (IPS) cells. Transmission properties of the two kinds of IPS-mode cells show that it is possible to decrease the driving voltage for the IPS-mode cell with a weak anchoring alignment surface. The response times of the PVCi-PVA cells are almost the same as those of the PVA-PVA cells, however, the measurement results of the relaxation times for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This anchoring effect may be similar to memory effect of the nematic LC on polymer alignment layers. [14][15][16][17][18] On increasing temperature, the anchoring molecules rotated toward the electric field and tended to recover the initial orientation after turning off the field. This can explain the time-dependent transmittances of the PB cell at high temperature shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This anchoring effect may be similar to memory effect of the nematic LC on polymer alignment layers. [14][15][16][17][18] On increasing temperature, the anchoring molecules rotated toward the electric field and tended to recover the initial orientation after turning off the field. This can explain the time-dependent transmittances of the PB cell at high temperature shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Uchida et al [17] developed a method in which the multi-parameter fit was not required. The voltage dependence of capacitance can be expressed as [7,[17][18][19] …”
Section: Methodsmentioning
confidence: 99%
“…The hysteresis characteristics were observed with increasing and decreasing voltages. The in-plane switching mode cell using the PVCi surface has also been reported to exhibit a hysteresis characteristic [33,34]. It has also been reported that the high viscosity of the gliding LC molecules on the surface caused a very slow response [35][36][37].…”
Section: V-t Curvesmentioning
confidence: 97%